Anti-poverty psychology - Carr, Stuart C. (International and Cultural Psychology, 2013)
Reducing poverty, whether globally or locally, has always comprised a set of complex critical tasks. But just as essential as the tasks is their underlying worldview: where formerly the emphasis was on changing institutions and thus changing people, the movement now is away from paternalistic remedies and toward culturally aware organizations and efforts to develop the untapped resources of people and their communities. Anti-Poverty Psychology traces the evolution of conceptualizations of poverty and its solutions, forcefully arguing for a higher level of current and future efforts. This visionary volume provides readers with a clear roadmap from goals (e.g., the Millennium Development Goals) to implementation that neither shames nor objectifies those being served. The author demonstrates how, in both research and the real world, progress is best achieved through systematic, cross-disciplinary, multi-perspective collaboration, alignment with local values, and greater accountability on the part of all involved. Coverage balances macro, meso and micro levels of analysis in such areas as:  Constructs of personality: beyond mythmaking and pathologizing. Building the socially responsible organization. The role of community in self-empowerment. Harnessing the potential of markets in poverty reduction. Minting media social capital The hidden psychology of international aid. Mobilizing human talent locally Developing research advocacy and its component skills. The perspective-widening stance and depth of insight found in Anti-Poverty Psychology gives it significance to audiences across disciplines, as in psychologists researching global development issues, academics interested in learning what motivates educators, community psychologists, and health professionals.